China under Xi Jinping : An Interdisciplinary Assessment - Dahl, Michał; Kupś, Hanna; Szatkowski, Maciej (Social Sciences E-Books Online, Collection 2024., 2024)
China under Xi Jinping: an Interdisciplinary Assessment provides a comprehensive review of Xi's reforms and his impact on the course taken by modern China, both domestically and internationally. The authors of the chapters - experts dealing with China in their daily academic or analytical work - formulate answers to the following questions: • How has China's political system changed under Xi Jinping? • What characterizes Xi as a politician? • What are the reasons for the success of China's economic transformation? • What's next for the Belt and Road Initiative? • How is Xi Jinping's China responding to challenges in terms of security policy, but also, i.e., climate protection and energy transition? • How is Chinese nationalism shaping up under Xi's rule? • How is Xi Jinping's cabinet responding to the domestic and international challenges? • What changes have occurred in Chinese culture since Xi took power?